2021
DOI: 10.3390/jcm10061248
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Macrophage/Monocyte-Endothelial Cell Crosstalk in the Liver: A Role for Trem-2

Abstract: Liver disease accounts for millions of deaths worldwide annually being a major cause of global morbidity. Hepatotoxic insults elicit a multilayered response involving tissue damage, inflammation, scar formation, and tissue regeneration. Liver cell populations act coordinately to maintain tissue homeostasis and providing a barrier to external aggressors. However, upon hepatic damage, this tight regulation is disrupted, leading to liver pathology which spans from simple steatosis to cirrhosis. Inflammation is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…The conditioned medium obtained from TREM2 + macrophages enhances transcriptional expression of collagen marker genes in hepatic stellate cells (HSCs) 20 . Therefore, TREM2 + macrophages have been suggested as SAMacs that regulate hepatic fibrogenesis 22 . However, the mechanisms of how TREM2 + macrophages control fibrotic scar formation in the liver is largely unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditioned medium obtained from TREM2 + macrophages enhances transcriptional expression of collagen marker genes in hepatic stellate cells (HSCs) 20 . Therefore, TREM2 + macrophages have been suggested as SAMacs that regulate hepatic fibrogenesis 22 . However, the mechanisms of how TREM2 + macrophages control fibrotic scar formation in the liver is largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…20 Therefore, TREM2 + macrophages have been suggested as SAMacs that regulate hepatic fibrogenesis. 22 However, the mechanisms of how TREM2 + macrophages control fibrotic scar formation in the liver is largely unclear. Here, we examined the gene profiles of heterogeneous hepatic macrophage populations and found that TREM2 + macrophages predominantly expressed MMPs to control hepatic scar formation with phenotypes of SAMac in fibrotic injured livers.…”
Section: Introductionmentioning
confidence: 99%
“…However, we also observed that some TREM2+ cells were not co‐localized with F4/80+ cells, which may be due the fact that TREM2 is expressed not only in F4/80+ cells like macrophages, but also in other F4/80‐ cells such as dendritic cells, hepatic stellate cells and adipocytes. 30 , 32 Additionally, the variety of F4/80+ cells may contribute to the discrepancy, as F4/80 + CD86+ cells represent M1 polarized macrophages which express low levels of TREM2, while F4/80 + CD206+ cells represent M2 polarized macrophages which may express higher levels of TREM2. However, further studies are needed to confirm whether macrophages with low TREM2 expression are indeed M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism that could control the proliferation of macrophages involves the triggering receptor expressed on myeloid cells 2 (TREM2). TREM2 is a single-pass transmembrane receptor of the immunoglobulin superfamily that binds phospholipids as well as anionic molecules, including bacterial products, DNA, and lipoproteins [ 112 , 113 ].…”
Section: Tissue Microenvironment and Self-renewal Of Macrophagesmentioning
confidence: 99%
“…Although most of the information about TREM2 are from microglia in central nervous system [ 115 ], TREM2 is expressed in TAMs and seems to play an immunosuppressive role in cancer [ 55 , 110 ]. An increase in TREM2 + macrophages has been observed in HCC [ 113 ] and in pancreatic ductal adenocarcinoma [ 116 ]. Martina M. et al [ 110 ] also demonstrated that Trem2 –/– mice exhibited resistance to tumor growth due to an alteration in macrophage subsets and an increase of intra-tumoral CD8 + T cells.…”
Section: Tissue Microenvironment and Self-renewal Of Macrophagesmentioning
confidence: 99%